Z-Isomers of (4α→6′′, 2α→O→1′′)-phenylflavan substituted with R′=R=OH. Conformational properties, electronic structure and aqueous solvent effects - Bentz, Erika Natalia (2016)
Fil: Bentz, Erika Natalia. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.